Academic literacy program implementation in an Ecuadorian University: a multinomial logit approach - Méndez Prado, Silvia Mariela; Alvarado Sánchez, María Isabel; Rosado Anastacio, Joel Alejandro (International journal of adolescence and youth, 2019)
The 'FCSHlee' program proposed by ESPOL Polytechnic University's School of Social and Humanistic Sciences (FCSH, acronym in Spanish), consisted in the implementation of a reading requirement of culturally enriching book by subject. This study shares the experience of an academic literacy initiative in the Ecuadorian university, ESPOL's case. The program aimed to enhance undergraduate students' cultural level as well as oral and written communication skills. We develop a significant sample (N = 387) of the students that were part of the program and collected the data through surveys after its completion. The study describes details of the program, its scope, implementation, statistics, and conditions. Among the careers studied at the FCSH, Economics was the one that had a bigger margin of appreciation towards the program, which is a factor that could indicate that these groups of students possess reading orientation given the analytical characteristics of their study program.